Earnings Persistence, Earnings Management and Stock Returns - Kpeli, P.A. (University Of Ghana, 2019)
This thesis examines the interactive effect of persistence in earnings and earnings management on stock returns. It employs both firm and macro-level data comprising of 39,490 listed firms from 1995 to 2013 across 45 countries. By employing different methodologies and estimation techniques on each research objective, the study provides the following empirical evidence: first, there is the presence of strong earnings persistence and a relatively low speed of adjustment. On the determinants of persistence of earnings, this study shows that low and least profitable firms manage their earnings. More so, the study identifies that macro-economic factors affect stock returns. Finally, this study identifies an insignificant relationship between the joint effect of earnings persistence and earnings management on stock returns. The study makes the following contributions to literature: First, the study provides evidence of strong profit persistence across industries and regions in both developed and emerging economies, however there are variations in the level of persistence across these industries and regions involved in the study. Additionally, the study provides evidence of earnings management among low and least profitable non-financial firms. Finally, the study identifies an insignificant relationship on the sensitivity between earnings persistence and earnings management on stock returns. In conclusion, the thesis supports the need for policy and regulations to guide the level of discretion provided by the reporting standards on managing earnings. More so, investors, should also consider other micro economic factors such as the size and leverage of the firm, the nature of intangible assets and the macroeconomic conditions in which the firm operates before making any economic decision.
MPhil. Accounting
Keywords: Information Asymmetry; Efficient Market Hypothesis (EMH); Stock Returns; Earnings Management